First implantation of retinal prosthesis in a patient with high myopia after surgery and rehabilitation program in Taiwan. Issue 7 (July 2019) - Hsu, Po-Cheng; Chen, Po-Yin; Chung, Yi-Shun; Lin, Tai-Chi; Hwang, De-Kuang; Chen, Shih-Jen; Kao, Chung-Lan
Abstract : The implantation of the Argus II retinal prosthesis system in a 54-year-old woman with retinitis pigmentosa who presented with an eye of long axial length at 26.82 mm was successful. Postoperative examination revealed a gap of 700 µm between the electrode array and the retina, which caused decreased visual perception. A modified strategy with quad and quinary electrode stimulation was introduced to generate higher perceptual thresholds. The patient experienced visual functional changes during the first half of the year after surgery, although no remarkable difference was observed in terms of implant–retina distance. Fibrosis around the tack developed and extended between the gap with the retina elevated from the tack toward the center array, 8 months after the surgery. Schisis of the retina developed and filled the gap, resulting in decreased threshold, and the strategy was then shifted back to single electrode stimulation mode. Rehabilitation program is an evolving process that depends on the distance between the array and the retina in the eye with staphyloma. This study first showed the implantation in a patient with high myopia who presented with long axial length after surgery and rehabilitation program in Taiwan.